CONCEPT OF RAKTAGNI WITH REFERANCE TO IRON METABOLISM AND ERYTHROPIOSIS - Chormore M Prashant; Waghulde S Sayali; Bangarwar Y Chandrashekhar (International Journal of Applied Ayurved Research, 2014)
The “Agni‟ occupies entire body, and various biotransformation’s are carried out in living body at all places. “Dhatwagni‟ is that part of Agni, which assimilates or synthesizes “Dhatu‟ of living body. Dalhan says, by Trividh parinaman, dhatu is converted into three parts by its own dhatwagni. Raktagni acts on Rakta poshakansha and transforms it into 1. Sthayi Rakta dhatu, 2.Poshakansha of mamsa dhatu and Upadhatu (Sira and kandara), 3.Its mala. Raktagni can be correlated in modern science to various substances (erythropoietin, apotransferrin, aconitase, B12 vitamin, folic acid etc) and biochemical reactions occurring in the process of iron metabolism and erythropoiesis.